Hereditary Anhidrotic Ectodermal Dysplasia - A case report (Anwer Khan Modern Medical College Journal, 2014)
Ectodermal dysplasia is a hereditary disorder that occurs as a consequence of disturbances in the ectoderm of the developing embryo. The triad of nail dystrophy, alopecia or hypotrichosis and palmoplantar hyperkeratosis is usually accompanied by a lack of sweat glands and a partial or complete absence of primary and/or permanent dentition. Ectodermal dysplasia is a rare genetic disorder and X-linked recessive inheritance is most commonly seen. But we are reporting a rare case of autosomal recessive inheritance of Ectodermal dysplasia in here. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18845 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 51-53